If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7(x + -2) = 2x + -5 Reorder the terms: 9 + -7(-2 + x) = 2x + -5 9 + (-2 * -7 + x * -7) = 2x + -5 9 + (14 + -7x) = 2x + -5 Combine like terms: 9 + 14 = 23 23 + -7x = 2x + -5 Reorder the terms: 23 + -7x = -5 + 2x Solving 23 + -7x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 23 + -7x + -2x = -5 + 2x + -2x Combine like terms: -7x + -2x = -9x 23 + -9x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 23 + -9x = -5 + 0 23 + -9x = -5 Add '-23' to each side of the equation. 23 + -23 + -9x = -5 + -23 Combine like terms: 23 + -23 = 0 0 + -9x = -5 + -23 -9x = -5 + -23 Combine like terms: -5 + -23 = -28 -9x = -28 Divide each side by '-9'. x = 3.111111111 Simplifying x = 3.111111111
| -3x-9=-3x+15 | | 8+x+6x=85 | | 3x+2y+z=-2 | | 32X^2+18= | | 10-5(x-3)=2x-8 | | 1/2-4=x-6 | | 81=6x+7x+3 | | -10(-7)-10y=10 | | 3x-11=5x-29 | | 3(v-1)+4v=3(v-1)+7 | | X^2+4xy-x^2=5 | | 5(4x+7)=-37+32 | | 1/2(x-11)=1/2 | | 9-7(x-3)=2x-10 | | 6(5x+1)=336 | | 3y-6=2(y+4) | | -27+3y=-9 | | 7-3(x-6)=5x-5 | | (1/4)y-(1/2)=(1/9) | | 4(6x+3)=300 | | 21-3x=4x | | 2x^6-10x^4+10=0 | | 4(6x+3)=3003 | | 4x=6.8 | | 4(x-1)-6=6x-2(4+x) | | 8(2x-6)=5(3x-7) | | f(x)=300x-5x^2+5 | | 3-4(x-3)=3x-12 | | 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 |